Transcription and proteome changes involved in re-innervation muscle following nerve crush in rats - Haotao Li; Wanqiong Yuan; Yijian Chen; Bofu Lin; Shuai Wang; Zhantao Deng; Qiujian Zheng; Qingtian Li (BMC Genomics, 2022)
Abstract Severe peripheral nerve injury leads to the irreparable disruption of nerve fibers. This leads to disruption of synapses with the designated muscle, which consequently go through progressive atrophy and damage of muscle function. The molecular mechanism that underlies the re-innervation process has yet to be evaluated using proteomics or transcriptomics. In the present study, multi-dimensional data were therefore integrated with transcriptome and proteome profiles in order to investigate the mechanism of re-innervation in muscles. Two simulated nerve injury muscle models in the rat tibial nerve were compared: the nerve was either cut (denervated, DN group) or crushed but with the nerve sheath intact (re-innervated, RN group). The control group had a preserved and intact tibial nerve. At 4 weeks, the RN group showed better tibial nerve function and recovery of muscle atrophy compared to the DN group. As the high expression of Myh3, Postn, Col6a1 and Cfi, the RN group demonstrated superior re-innervation as well. Both differentially expressed genes (DEGs) and proteins (DEPs) were enriched in the peroxisome proliferator-activated receptors (PPARs) signaling pathway, as well as the energy metabolism. This study provides basic information regarding DEGs and DEPs during re-innervation-induced muscle atrophy. Furthermore, the crucial genes and proteins can be detected as possible treatment targets in the future.